2023
DOI: 10.3390/buildings13010155
|View full text |Cite
|
Sign up to set email alerts
|

Extended Reality for Safe and Effective Construction Management: State-of-the-Art, Challenges, and Future Directions

Abstract: Safe and effective construction management requires tools for reducing delays, eliminating reworks, and avoiding accidents. Unfortunately, challenges still exist in current construction practices for enabling real-time interactions among project participants, field discoveries, and massive data. Extended reality (i.e., XR) could help to establish immersive and interactive virtual environments that enable real-time information exchange among humans, cyber processes, and physical environments during construction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 80 publications
0
8
0
Order By: Relevance
“…As of October 2023, PRISMA, introduced in 2009 [72], has been adopted in over 60,000 publications across various disciplines. In review articles featured in journals such as "Buildings" [2], "Forests" [69], "Virtual Reality" [70], and "Automation in Construction" [73], a similar approach leveraging PRISMA's threestage or four-stage flow diagram for data selection has been observed. This study aligns with the updated PRISMA three-stage flow diagram from 2020 [74] for the screening of literature data.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…As of October 2023, PRISMA, introduced in 2009 [72], has been adopted in over 60,000 publications across various disciplines. In review articles featured in journals such as "Buildings" [2], "Forests" [69], "Virtual Reality" [70], and "Automation in Construction" [73], a similar approach leveraging PRISMA's threestage or four-stage flow diagram for data selection has been observed. This study aligns with the updated PRISMA three-stage flow diagram from 2020 [74] for the screening of literature data.…”
Section: Methodsmentioning
confidence: 99%
“…The Log-Likelihood Ratio (LLR) is one of the clustered tag word extraction algorithms provided by Cite Space 6.2.R6 for extracting research terms at different locations in citing documents. Compared with other clustering algorithms, LLR emphasizes the research characteristics and is more suitable for the use requirements [2]. Utilizing the LLR algorithm within the clustering analysis, seven major research clusters (#0-#6) were identified.…”
Section: Application Scenario Analysismentioning
confidence: 99%
See 3 more Smart Citations